Upaya Meningkatkan Kemampuan Shootting Dalam Permainan Sepak Bola Dengan Metode Permainan Target Pada Siswa Kelas XSMK Methodist Tanjung Morawa - Alvaro Kurniawan Zai; Ignasius Ivan Kurnia Ndruru; Abdul Latif Rusdi Hasibuan Rusdi Hasibuan (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
This study aims to improve shooting skills in soccer through the implementation of a target game method among Grade X students at SMK Methodist Tanjung Morawa during the 2025/2026 academic year. The identified problem was the students' low level of shooting proficiency, which resulted in suboptimal performance during soccer matches. This study employed Classroom Action Research (CAR) conducted over two cycles. Each cycle consisted of planning, action implementation, observation, and reflection. The research subjects were 20 Grade X students from SMK Methodist Tanjung Morawa. The instruments used included a shooting skills test and a student activity observation sheet. The results showed that in Cycle I, 10 students (50%) achieved mastery, whereas in Cycle II, the number of students achieving mastery increased to 18 (90%). An improvement in shooting ability was observed, although some technical errors persisted. Instructional improvements in Cycle II yielded more optimal results, characterized by enhanced accuracy, power, and coordination in shooting movements, enabling the majority of students to achieve mastery. Beyond improving learning outcomes, the target game method also fostered increased motivation, active participation, cooperation, and self-confidence among students during the learning process. In conclusion, the target game method is effective for improving soccer shooting skills among Grade X students at SMK Methodist Tanjung Morawa. This method serves as an innovative, engaging, and student-centered alternative for physical education instruction, capable of enhancing the quality of both the learning process and learning outcomes.